BOKOA SIMBOL KEBUDAYAAN MASYARAKAT REJANG DALAM KARYA SENI GRAFIS - TRI WIRA SANDI, Drs. Yusron Wikarya, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
The final creation of the work was aimed at visualizing cocoa as a cultural symbol of the Rejang community in Bengkulu in graphic art. Displays various types of bokoa, which are now rarely used. The method of embodying this final work is through five stages, namely: Preparation, Elaboration, Synthesis, Realization of concepts, and stages of completion. The author succeeded in realizing 10 works under the title: Bokoa iben, Bokoa tangkai,Bokoa sarau, Bokoa serampi, Bokoa bungo, Bokoa selepai, Bokoa Keruntung, Bokoa sirih, Bokoa pane tuguk, Bokoa selebau.Keywords: Bokoa, Symbol of Culture, Graphic Arts.